2022
DOI: 10.1097/mot.0000000000000993
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in solid organ transplant: a review

Abstract: Purpose of reviewInfective endocarditis remains an uncommon disease with significant morbidity and mortality. In the last two decades, progress has been made describing the unique aspects of infective endocarditis in solid organ transplant (SOT) recipients. Recent findingsIncidence of infective endocarditis in SOT is higher when compared with the general population. End-stage organ dysfunction, diabetes mellitus, older age, and prior intravenous lines have been identified as risk factors predisposing to infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In this prospective study, the technique showed an accuracy of 81.95%, a specificity of 86.92%, a sensitivity of 73.33%, an NPV of 84.96%, and a PPV of 76.39% [87]. 18 F-FDG PET/CT is based on the accumulation of a radioactively labeled glucose analog ( 18 F-FDG) in cells with a large number of metabolically active glucose transporters expressed on their cell surface-activated inflammatory cells (macrophages, leukocytes, and lymphocytes) [88]. Heterogeneous uptake within the heart may be related to infection [89].…”
Section: Imaging Infective Endocarditis By Using Novel Techniquesmentioning
confidence: 70%
See 2 more Smart Citations
“…In this prospective study, the technique showed an accuracy of 81.95%, a specificity of 86.92%, a sensitivity of 73.33%, an NPV of 84.96%, and a PPV of 76.39% [87]. 18 F-FDG PET/CT is based on the accumulation of a radioactively labeled glucose analog ( 18 F-FDG) in cells with a large number of metabolically active glucose transporters expressed on their cell surface-activated inflammatory cells (macrophages, leukocytes, and lymphocytes) [88]. Heterogeneous uptake within the heart may be related to infection [89].…”
Section: Imaging Infective Endocarditis By Using Novel Techniquesmentioning
confidence: 70%
“…The incidence of IE is also higher in a population of solid organ transplant recipients compared to the general population. Staphylococci and enterococci represent the most frequently isolated pathogens (more common with HAIE [18]).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The Enterococcus species (11%) and Candida species (6%) represent other common agents. Fungal infections accounted for the most frequent etiologic agent within 30 days of transplantation (60%), while bacterial infections caused the majority of cases (80%) after this period [ 46 , 47 , 48 , 49 ].…”
Section: Microbiological Burden Of Infective Endocarditis: a Changing...mentioning
confidence: 99%